THE ROLE OF INDONESIAN YOUTH IN PROMOTING ECOTOURISM POLICY: A POLITICAL SOCIOLOGY REVIEW - Pikardo, Ronaldo; Zhan, Fuzy Firda; Ruspandi, Alvein; Asy’ari, Asy’ari (Journal of Social Politics and Governance (JSPG), 2024)
The ecotourism development strategy is not only the responsibility of the central and regional governments but also all levels of society, including the younger generation. This research aims to examine the role of Indonesian youth in pushing ecotourism policy from a political sociology perspective. Through qualitative descriptive methods with data obtained from literature studies, this research found that youth play a role in destination management, promotion via social media, and support for ecotourism policies. Youth also play a social control role and support participation in policy meetings. Apart from that, it is also known that social and political factors influence the role of youth in ecotourism development, namely social factors and political factors. However, challenges such as lack of promotion and participation of local communities need to be addressed. Therefore, collaborative efforts are required between youth, government, and society to overcome these obstacles and maximize the potential of ecotourism in Indonesia.